Food vending: adaptation under difficult circumstances - Muzvidziwa, Victor N. (Journal of Social Development in Africa, 2016)
The respondents discussed in this article depended on food vending as their main source of income. To succeed in this activity requires shrewd marketing and hard work. For the majority food vending was basically a hanging on and coping strategy, offering very limited surplus for investment. Food vending allowed them merely to stay in town while maintaining a foot in their home villages. The paper presents both a descriptive and an analytical account of food vending activities by female heads of households in Masvingo. The officially imposed constraints on food vending demonstrate the existence of competing and conflicting rationalities between male decision-makers and poor women. The inter -connections between food vendors and the formal markets are noted.